"Play of lmagination" - Aim or Means? - Liucinski, Kazimierz; Zubkov, Jevgenij (Respectus Philologicus, 2004)
This article concentrates on speech as play of imagination. It discusses various aspects of verbal communication in the context of needs and aims. The main objective of this article is to answer the question whether everything what we say is an aim or just means. Therefore, it provides the analysis of lexical units selected from various social and professional environments in order to check whether the produced discourse is always intentional or emotional. A special attention was paid to the analysis of the subculture languages in order to compare the function of speech in different social groups. Another important issue discussed in this article is the question of English borrowings in Russian. Both business English terms and colloquial phrases were described and compared with the corresponding ones in German. The results of the conducted investigation allow us to provide an answer to the initial question that speech cannot be perceived as either the aim or the means. It is a perfect combination just to become means with the aim.